DEVELOPMENT OF HYDRAULIC CONCEPTUAL MODEL FOR CONSTRUCTED STORMWATER WETLAND - Mangangka, Isri (JURNAL ILMIAH MEDIA ENGINEERING, 2014)
Artificial rainwater wetlands are manmade water bodies, shallow with dense vegetation that lead toreduce volume and peak discharge of runoff through evaporation, infiltration and retention. Built artificial wetlands are also known as efficient stormwater treatment devices, especially when rainwatercontains high concentrations of dissolved pollutants that cannot be released by other stormwatertreatment devices. Researchers have noted that the process of purifying the stormwater in the builtwetland is influenced by a number of hydraulic factors. In previous studies, the influential hydraulic factors have been developed using a lumped model. However, these influential hydraulic factors may vary during an event. Therefore, their effect on reducing stormwater pollutant may vary with their development. Variations of hydraulic factors during a rain event can only be generated using a detailed modelling approach. For this reason, a conceptual modelling approach needs to be developed to replicate the hydraulic conditions in the wetland. The hydraulic conceptual model developed is calibrated using trial and error procedures by comparing outflow models with measurable outflow data. The accuracy of the developed model was also analysed using a well-known statistical analysismethod developed based on regression analysis techniques. The analysis results show that the developed model is considered satisfactory, indicating that the approach used to develop the model is appropriate.